AN ANALYSIS OF CODE SWITCHING USED IN THE ENGLISH FOR SPECIFIC PURPOSES CLASS AT STATE POLYTECHNIC OF BENGKALIS - Ristra, Pretti; Arum Budiana, Agnes (INOVISH JOURNAL, 2024)
This study examines the phenomenon of code switching within the context of English for Specific Purposes (ESP) classes at the State Polytechnic of Bengkalis. Code switching, the alternation between languages or language varieties within discourse, is analyzed to understand its frequency, functions, and implications in enhancing language learning environments. The research employs qualitative methods, including classroom observations and interviews with and students. Findings reveal that code switching is a prevalent practice in ESP classrooms, serving various communicative and pedagogical purposes such as clarification, emphasis, and cultural integration. The study underscores the complex role of code switching in language education, suggesting implications for language policy and teaching strategies in similar educational settings.